Connecting the Dots: Resolving the Bone Marrow Niche Heterogeneity - Dolgalev, Igor; Tikhonova, Anastasia N. (Frontiers in Cell and Developmental Biology, 2021)
Single-cell sequencing approaches have transformed our understanding of stem cell systems, including hematopoiesis and its niche within the bone marrow. Recent reports examined bone marrow microenvironment at single-cell resolution at steady state, following chemotherapy treatment, leukemic onset, and aging. These rapid advancements significantly informed our understanding of bone marrow niche heterogeneity. However, inconsistent representation and nomenclature among the studies hinder a comprehensive interpretation of this body of work. Here, we review recent reports interrogating bone marrow niche architecture and present an integrated overview of the published datasets.